Students Anxiety Experiences during COVID-19 in Nepal - Dangal, M.R.; Bajracharya, L.S. (Kathmandu University Medical Journal, 2020)
Background COVID-19 started in China and has spread throughout the world since December 2019. The pandemic has not only brought the risk of morbidity and mortality from infection but also psychological burden. Objective To find out the psychological impacts of COVID-19 on students from high schools, colleges and universities in Nepal, along with examining the association between socio-demographic and other related variables and level of anxiety in the students. Method This study sampled students from Nepal using convenience sampling and responded to a quantitative questionnaire that included the 7-item Generalized Anxiety Disorder Scale (GAD-7) and other basic information. Finally, 105 respondents were included in the final analysis (100% response rate). Convenient sampling technique was used to gather the sample. Result The results indicated that 18.1% of the respondents were experiencing severe anxiety, 22.9% moderate anxiety, and 25.7% mild anxiety. Moreover, females were more prone to anxiety as compared to males. The results of correlation analysis indicated that economic effects, and delays in academic activities, were positively associated with anxiety symptoms (p < .05). However, social support was negatively correlated with the level of anxiety (p < .001). Conclusion It is recommended that the mental health of students should be monitored during public health emergencies, such as this one. This study examines the psychological impacts of COVID-19 among the college students in Nepal.